2015
DOI: 10.1186/s12958-015-0091-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of cumulus gene expression of GJA1, PRSS35, PTX3, and SERPINE2 with oocyte maturation, fertilization, and embryo development

Abstract: BackgroundGJA1 and PTX3 were proposed as gene markers for oocyte and embryo developmental competence, while SERPINE2 was reported to be associated with pregnancy outcome. PRSS35, which is exclusively expressed in the ovary, may be correlated with oocyte competence. This study was conducted to evaluate the correlation of cumulus GJA1, PRSS35, PTX3, and SERPINE2 gene expression levels with oocyte maturation, fertilization, and early embryo development.MethodsIn total, 308 cumulus cell samples separated from indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
46
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 41 publications
(64 reference statements)
7
46
2
1
Order By: Relevance
“…In contrast, we observed higher mRNA levels of CX43 in GCs of below median samples. Although we did not observe differences in CX43 mRNA levels between GCs samples of below versus above median blastocyst rates, previous studies in humans revealed conflicting results when correlating CX43 mRNA expression in cumulus cells with oocyte competence for embryo development and quality (Feuerstein et al, 2007;S. H. Li et al, 2015;Wang, Tong, El-Gehani, Tekpetey, & Kidder, 2009).…”
Section: Discussioncontrasting
confidence: 91%
“…In contrast, we observed higher mRNA levels of CX43 in GCs of below median samples. Although we did not observe differences in CX43 mRNA levels between GCs samples of below versus above median blastocyst rates, previous studies in humans revealed conflicting results when correlating CX43 mRNA expression in cumulus cells with oocyte competence for embryo development and quality (Feuerstein et al, 2007;S. H. Li et al, 2015;Wang, Tong, El-Gehani, Tekpetey, & Kidder, 2009).…”
Section: Discussioncontrasting
confidence: 91%
“…The expression levels of several genes in cumulus cells are associated with oocyte developmental competence . In the present study, the effect of FF on the cumulus cells was evaluated by determining the expression of marker genes.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the expression levels of the PFKP and PRDX3 genes in cumulus cells are associated with good‐quality embryos in humans; this study's results showed that the expression levels of these genes were higher in the cumulus cells that had been cultured in FF medium. GJA1 encodes connexin 43, a gap junction protein, and low expression levels of GJA1 in cumulus cells are associated with oocyte maturity . In addition, low expression levels of GJA1 in cumulus cells are associated with high developmental competence in human oocytes .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations